The nursing school of Natal and the University Hospital Onofre Lopes - Djailson José Delgado Carlos; Raimunda Medeiros Germano (Rev Rene)
The present study has an historic and qualitative focus with the purpose of documenting the history of the Nursing School of Natal and its relationship with the University Hospital Onofre Lopes. The empirical investigation was based on a review of the following documents: reports, mission statements, letters, regulations, statutes, laws, decrees, testimonies and interviews with people who have a living memory of its history. It postulates that the School at the Hospital slowly and gradually transformed the picture of Nursing at the institution, in so far as it absorbed the professionals it formed. Such qualifi cation became the most incisive when, after the federalization of the University of Rio Grande do Norte, in 1960, the director of the School took on, as well, the direction of the Hospital. This doubled responsibility converged to favor the intensifi cation of training students to become technical assistants in Nursing.